Multinationality and Performance Patterns in Advanced and Emerging Markets - Martin, Thomas Christopher (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2021)
This longitudinal research focuses on measuring multinationality of the firm, country, and industry, and estimating the relationship between said level of multinationality, and the firms' performance. My unique dataset consists of sales data from Thompson Reuters' Datastream, and hand collected subsidiary data, enabling the measurement of multinationality using the Alan Rugman's Triad model, and a more recent model by Aggarwal, Berrill, Hutson, and Kearney, the ABHK model. The study of firm level multinationality in the 1990's and 2000's has enforced the hypothesis that firms are regional by nature through Rugman's analysis of Fortune 500 firms. The majority of that dataset is comprised of firms from the United States, Western Europe, or Japan, who record a large portion of their sales to those regions, thus coined the "Triad" regions by Ohmae (1985). This finding still holds true as trading abroad occurs to the continents of North America, Europe, and Asia by a greater number of firms when compared to South America, Africa, and Oceania. Concurrently, firms are both trading and investing at a rapid pace to countries in the latter three continents, concluding the Triad model to once be an accurate multinationality measuring model in the 1990's and early 2000's, an out of date model to measure a firms' multinationality in today's global economy. I preform an analysis of a 2,427 firms' multinationality using the Triad and ABHK models. I then determine whether a relationship exists between the firms' performance and its multinationality using a regression analysis. The performance-multinationality literature is divided with a wide range of measures being used in the regression model. I use three measures of multinationality; Triad model, ABHK model, and foreign sales percentage, and three measures of firm performance; return on assets, return on equity, and total return index, providing a thorough analysis on the subject matter. The results provide evidence of the ABHK model as the most appropriate measure of multinationality, and total return index as the measure of performance that gives the most significant regression results. Performance and multinationality have a significantly positive relationship when measured by ROA and the ABHK model for South American and African firms, while the remaining four continents of the world measure a significantly negative relationship. Analyzing the dataset, I select a positivist functionalist approach as the most appropriate for the research. My research objectives are to determine if patterns exist in the multinationality of advanced and emerging market firms and if the performance of the firm increases or decreases as multinationality changes. This research makes an empirical, methodological, and data contribution to academia.
APPROVED
Keywords: multinationality; firm performance; emerging markets